A high energy density asymmetric supercapacitor utilizing a nickel phosphate/graphene foam composite as the cathode and carbonized iron cations adsorbed onto polyaniline as the anode. Issue 21 (26th March 2018) - Mirghni, A. A.; Madito, M. J.; Oyedotun, K. O.; Masikhwa, T. M.; Ndiaye, N. M.; Ray, Sekhar. J.; Manyala, N.
Abstract : This work presents the effect of different contents of graphene foam (GF) on the electrochemical capacitance of nickel phosphate Ni3 (PO4 )2 nano-rods as an electrode material for hybrid electrochemical energy storage device applications. Abstract : This work presents the effect of different contents of graphene foam (GF) on the electrochemical capacitance of nickel phosphate Ni3 (PO4 )2 nano-rods as an electrode material for hybrid electrochemical energy storage device applications. Pristine Ni3 (PO4 )2 nano-rods and Ni3 (PO4 )2 /GF composites with different GF mass loadings of 30, 60, 90 and 120 mg were synthesised via a hydrothermal method. The electrochemical behavior of pristine Ni3 (PO4 )2 and Ni3 (PO4 )2 /GF composites were analysed in a three-electrode cell configuration using 6 M KOH electrolyte. The Ni3 (PO4 )2 /90 mg GF composite sample exhibited the highest specific capacity of 48 mA h g −1 at a current density of 0.5 A g −1 . The electrochemical behavior of the Ni3 (PO4 )2 /90 mg GF composite was further analysed in a two-electrode hybrid asymmetric device. A hybrid asymmetric device was fabricated with Ni3 (PO4 )2 /90 mg GF as the cathode and carbonized iron cations (Fe 3+ ) adsorbed onto polyaniline (PANI) (C-FP) as the anode material (Ni3 (PO4 )2 /90 mg GF//C-FP) and tested in a wide potential window range of 0.0–1.6 V using 6 M KOH. This hybrid device achieved maximum energy and power densities of 49 W h kg −1 and 499 W kg −1, respectively, at 0.5 A g −1 and had long-term cycling stability.